Utilization of Cassava-Jicama Composite Flour in Making Gluten-Free Biscuits with Different Types of Fats - Richirose, Richirose; Soedirga, Lucia Crysanthy (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Biscuits are a commonly consumed bakery product typically using wheat flour as a primary ingredient, rendering them unsuitable for gluten-intolerant consumers. Using cassava as a gluten-free alternative for composite flour in bakery products has been proven effective. Furthermore, jicama, which has high total dietary fiber contents, including inulin, can enhance total dietary fiber content. However, high-fiber ingredients can often produce a tough texture. To address this, fats such as butter and margarine are typically used to enhance the texture of baked products, although the use of shortening still needs to be explored. Both margarine and shortening are vegetable-based, making them more widely consumable. The production of jicama flour and gluten-free biscuits was the focus of this study. This study uses a completely randomized design with two factors: the ratio of composite flour (100:0, 90:10, 80:20, 70:30, 60:40) and the type of fat (margarine and shortening). Analyses were performed on the gluten-free biscuits to determine the total dietary fiber, inulin, fat, moisture, spread ratio, color and hardness. Results indicated that biscuits made with shortening with a flour ratio of 90:10 of cassava to jicama flour are the best formulation, yielding 2.54±0.00% inulin, 6.50±0.10% total dietary fiber, 19.88±0.17% fat, 2.20±0.10% moisture content, 10.03±0.20 spread ratio, lightness (L*) value of 52.53±0.37, °Hue value of 66.78±0.51, and 869.88±16.07 g hardness. This study shows that jicama flour can be an alternative to producing composite flour for gluten-free products. Shortening, which is not commonly used in biscuit making, may be considered an alternative fat source.